Does Dividend Policy Mediate the Relationship Between Financial Performance and Company Value? - Steward Gani; Rasinta Ria Ginting; Enda Noviyanti Simorangkir (Облік і фінанси, 2022)
The impact of financial performance and dividend policy on company value is the subject of numerous studies in corporate finance, although the findings are still conflicting. Therefore, this study aims to analyze factors affecting the company values of manufacturing companies listed on the Indonesia Stock Exchange. The sample of this study is 31 manufacturing companies that were listed on the Indonesian Stock Exchange (IDX) in 2016-2020. This study uses quantitative secondary data, particularly financial reports published by manufacturing companies on the Indonesian Stock Exchange (IDX) website (https://www.idx.co.id/). Structural Equation Modeling with Partial Least Square (SEM-PLS) is the analytical model used in this study. The independent variables in this study are Liquidity (X1) (represented by the Current Ratio (CR)), Leverage (X2) (represented by the Debt to Equity Ratio (DER)), and Profitability (X3) (represented by the Return on Assets (ROA)). The dependent variable in this study is Company Value (Y), represented by the Price-to-Book Value (PBV). The mediating variable in this study is Dividend Policy (Z), represented by the Dividend Payout Ratio (DPR). The results show that liquidity does not affect company value; profitability and leverage have effects on company value with a positive direction; dividend policy does not affect company value; liquidity, leverage, and profitability do not affect dividend policy, and the relationship between liquidity, leverage, and profitability and company value cannot be mediated by dividend policy. This study contributes to the literature by giving a deeper understanding of factors affecting company value. Companies should optimize leverage and maximize profitability to maximize company value.